IMPLEMENTASI MODEL PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPS KELAS III SEKOLAH DASAR - Sabahiyah (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to increase students’ understanding of the social studies concept in class III at SDN 4 Mamben Daya by using the talking stick learning model. This research is a classroom action research, and was carried out for two cycles. Each cycle consists of planning, acting, observing and reflecting. The subjects in this study were class III students at SDN 4 Mamben Lauk with a total of 23 students, consisting of 12 boys and 11 girls. Data on students’ social studies concept comprehension were collected using oral and written test techniques in the form of essays. After the data on students’ social studies concept mastery was collected, the data was then analyzed descriptively. Data on the results of understanding the IPS concept in cycle I averaged 69.91 classes with a classical completeness of 70%. Whereas in cycle II the class average was 71.87 with classical completeness of 91%. From the results of the data analysis it can be concluded that the implementation of the talking stick learning model can increase the understanding of the IPS concept.